2018
DOI: 10.1016/j.soilbio.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term increased N deposition on tropical montane forest soil N2 and N2O emissions

Abstract: This is a repository copy of Effects of long-term increased N deposition on tropical montane forest soil N and N O emissions ₂ ₂ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 60 publications
(89 reference statements)
3
26
1
Order By: Relevance
“…We investigated N 2 production rates and processes across ∼2,500 km continental shelf sediment transect along coastline in eastern China (Figure 1) and found that denitrification process dominated N 2 production with the average relative contribution of 90% and ranged from 0.03 to 9.73 nmol N 2 g −1 h −1 (Figure 1 and Figure S3 in Supporting Information S1). Our measured N 2 production rates by denitrification were comparable to previous studies in marine and estuarine sediments (Gao et al., 2016; Lin et al., 2017) and in terrestrial ecosystems (Gu et al., 2017; Tang et al., 2018; Wu et al., 2018; Xi et al., 2016). Additionally, sediment denitrification rates in the studied regions are higher than the rates from sea water columns in some coastal regions (Dalsgaard et al., 2013; Seitzinger, 1988), confirming the estimate from models that sedimentary denitrification rate may be higher than suboxic zones (DeVries et al., 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We investigated N 2 production rates and processes across ∼2,500 km continental shelf sediment transect along coastline in eastern China (Figure 1) and found that denitrification process dominated N 2 production with the average relative contribution of 90% and ranged from 0.03 to 9.73 nmol N 2 g −1 h −1 (Figure 1 and Figure S3 in Supporting Information S1). Our measured N 2 production rates by denitrification were comparable to previous studies in marine and estuarine sediments (Gao et al., 2016; Lin et al., 2017) and in terrestrial ecosystems (Gu et al., 2017; Tang et al., 2018; Wu et al., 2018; Xi et al., 2016). Additionally, sediment denitrification rates in the studied regions are higher than the rates from sea water columns in some coastal regions (Dalsgaard et al., 2013; Seitzinger, 1988), confirming the estimate from models that sedimentary denitrification rate may be higher than suboxic zones (DeVries et al., 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Codenitrification, which can occur by both fungi and bacteria, can produce N 2 O and N 2 through reduction of nitrite by other N compounds, such as hydroxylamine and salicylhydroxamic acid (Spott & Florian Stange, 2011). Therefore, codenitrification can produce 29 N 2 in the presence of 15 NO 3 − , resulting in higher 29 N 2 production rate and anammox rate in the 15 NO 3 − + NH 4 + incubation than in the NO 3 − + 15 NH 4 + incubation (Tang et al., 2018; Xi et al., 2016). Our results suggest codenitrification may be a possible N 2 production process in coastal sediments, with the average relative contribution of 4.7% (Figure S3 in Supporting Information S1).…”
Section: Discussionmentioning
confidence: 99%
“…N 2 O emission is an important pathway of the soil nitrification-denitrification process [37,38]. N addition significantly increased N 2 O emission in our study, which was consistent with the results from previous studies [16,39,40].…”
Section: Effects Of the Quantity And Frequency Of N Addition On Greensupporting
confidence: 93%
“…Recent studies have suggested that chronic N deposition into temperate habitats may offer sufficient N inputs to these ecosystems (Hedin et al, 2009) causing N saturation (Nair, 2014;Tian et al, 2016). There is evidence that these N saturation effects may also be impacting tropical environments (Chen et al, 2016;Tang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%